Synthesis, Characterization and Antimicrobial Activity Studies of 1- and 2-[4-(4-Chloro phenyl)phenyl methyl- 1-piperazinyl]sulphonyl naphthalenes - DAYALAN, A.; SUNEEL MANOHAR BABU, C.; VISWESWARAN, V. (Asian Journal of Chemistry, 2010)
Two isomeric naphthalene sulphonyl compounds viz., 1-and 2-[4-(4-chloro phenyl)phenyl methyl-1-piperazinyl] sulphonyl naphthalenes were synthesized from p-chloro benzophenone and naphthalene as the main starting materials with piperazine bridge and characterized by spectral methods. Their antimicrobial activities were also studied.